Report on Farmer-to-Farmer exchange visit in the Agroecological Living Landscape (ALL) - Rudiger, Udo (2024)
The report describes the different technologies farmers have seen and exchanged about with other farmers of different organizations. It has a summary chapter on lessons learned and opportunities of collaboration between farmer organizations